K-12 schools’ campus, food service, and transportation directors’ COVID-19 and current challenges - G. S. Prakasha; Trent Grundmeyer; Sivaselwam Arulnesan; S. Thirumalesha; C. S. Gururaja (Journal of Education and Learning (EduLearn), 2026)
This study examines the COVID-19 experiences of K-12 school campus directors, especially in terms of building and grounds, transportation, and food services from the Midwestern United States. The COVID-19 pandemic has changed to online education mode and implemented safety protocols to ensure equitable access to K-12 education. School directors play a crucial role in United States’s school administration. The researchers used a mixed method research design and purposive sampling. The sample included 9 school-grounds directors, 34 food service directors, and 31 transportation directors. A 5-point Likert-type questionnaire was prepared by the researchers to collect the relevant data for the study. The data were analyzed using descriptive statistics and thematic analysis. While revealing their experiences, various school directors mentioned that key challenges are reliable sources of information for them to work, inequities in resource allocation, finance allocation, and lack of professional training. The survey highlighted the need for several resources, including federal and state funding, teacher professional development programs, and community partnerships that support K-12 education. School directors addressed challenges regarding transportation, buildings, grounds, and food services during COVID-19. The study revealed the need for systemic policy changes and communication resources to create resilient and adaptive learning environments for K-12 education. Eventually, the study recommended that policymakers and educational leaders bring changes to K-12 infrastructure to withstand crises like COVID-19.